The Russia-Ukraine war, soaring food prices, and the Turkish economy: insights from computable general equilibrium - Ozturk, Ozcan; Faizi, Bushra (Frontiers in Environmental Science, 2023)
The ongoing war between Russia and Ukraine has led to considerable human suffering and raised concerns regarding the potential implications for the global economy. Turkiye, as a neighboring country and a major player in the region, maintains close ties with Ukraine and Russia and heavily relies on agricultural imports from both countries making it susceptible to market shocks caused by the war. In this research paper, we examine the economic impact of war-induced soaring food prices on the Turkish economy using a Computable General Equilibrium (CGE) model, which is a widely used tool for simulating the effects of shocks and policy changes on a country's economy. We considered two utility functions with varying elasticity parameters to explore both micro-level and macro-level impacts of the price shock, encompassing household demand, industrial production, price and trade dynamics, income, investment, and welfare implications. The findings reveal significant effects on agricultural imports of crops (wheat, maize, barley, rice, and cereal grains), fruit and vegetables, and oil products, leading to an increase in both import and domestic prices, resulting in food inflation in the country. Additionally, the findings show that while the trade balance for the agricultural sector improved, the services, manufacturing, and forestry sectors have experienced an increased trade deficit. Furthermore, the war has caused a decline in foreign direct investment flowing into the country. Finally, the war-led price shock resulted in an estimated income loss of 0.2 or 0.8 percent of real GDP depending on the utility function, and a significant welfare loss. Based on these findings, several policy recommendations were discussed. The findings of the study highlight the importance of considering the interplay between food prices and micro and macroeconomic indicators.